2020
DOI: 10.1016/j.jallcom.2019.152721
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of reduced graphene oxide thin film as an efficient electron conductive interlayer in a proven heterojunction photoanode for solar-driven photoelectrochemical water splitting

Abstract: Although bismuth vanadate (BiVO4) has shown excellent photoelectrochemical (PEC) properties and is a good candidate of photoanode materials, the solar-driven PEC water splitting performance is still remained below its full potential due to the fast recombination and sluggish charge mobility of photogenerated charge carriers. Previously, we have communicated a proven Type II staggered vanadium pentoxide (V2O5)/BiVO4 heterojunction photoanode that could improve the photocurrent density. This study aimed to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This important work provides a new entry to the use of g-C3N4 in the design of new and efficient water division systems [224]. Chong et al [230] reported V2O5/rGO/BiVO4 heterojunction (Figure 8) as an efficient photo-electrochemical water division photoanode. .…”
Section: Water Splittingmentioning
confidence: 94%
See 1 more Smart Citation
“…This important work provides a new entry to the use of g-C3N4 in the design of new and efficient water division systems [224]. Chong et al [230] reported V2O5/rGO/BiVO4 heterojunction (Figure 8) as an efficient photo-electrochemical water division photoanode. .…”
Section: Water Splittingmentioning
confidence: 94%
“…The majority of previous studies on the conversion of NOx gases have involved different lasers [254], spectroscopic (such as infrared (IR), [255], and chemiluminescence (CL) [256] or electrochemical techniques [257] for the detection of NOx reaction products. The use of high-resolution MS for biomedical applications to detect NO [230] and indirectly semiconducting metal oxides [231] has been described. The main cause of water pollution is industrial wastewater discharge.…”
Section: Nox Conversionmentioning
confidence: 99%